COMT Val158Met Polymorphism Modulates Cognitive Effects of Dietary Intervention - Witte, A. Veronica; Jansen, Stefanie; Schirmacher, Anja; Young, Peter; Flöel, Agnes (Frontiers in Aging Neuroscience, 2010)
A common single nucleotide polymorphism in the gene encoding catechol-O-methyltransferase (COMT), Val158Met, is thought to influence cognitive performance due to differences in prefrontal dopaminergic neurotransmission. Previous studies lend support for the hypothesis that the “at-risk” genotype comprising two Val-alleles (low dopamine) might benefit more from plasticity-enhancing interventions than carriers of one or two Met-allele. This study aimed to determine whether the response to dietary interventions, known to modulate cognition, is dependent on COMT genotype. Blood samples of 35 healthy elderly subjects (61.3 years +/- 8 SD; 19 women, 16 men, BMI: 28.2 kg/m² +/- 4 SD) were genotyped for COMT Val158Met by standard procedures (Val/Val = 6; Val/Met = 20; Met/Met = 9). Subjects had previously completed a randomized controlled trial investigating the effects of caloric restriction (CR) or enhancement of unsaturated fatty acids (UFA) on immediate and delayed verbal recognition memory. Homozygous Val/Val-carriers had significantly lower memory scores than Met-carriers at baseline (p < 0.001). Significant interactions of genotype and dietary intervention with regard to cognition were found: CR- and UFA enhancement-induced memory improvements of Val/Val-carriers were considerably greater than those of Met-carriers (ANOVA p’s < 0.02). The current study shows for the first time that cognitive effects of dietary interventions are dependent on COMT Val158Met genotype. Our findings lend further support to the hypothesis that an “at risk”-genotype might benefit more from plasticity-enhancing interventions than the “not at risk”-genotype. This might help to develop individualized therapies in future research based on genetic background.